An innovative pre-targeting strategy for tumor cell specific imaging and therapy. Issue 35 (19th August 2015) - Qin, Si-Yong; Peng, Meng-Yun; Rong, Lei; Jia, Hui-Zhen; Chen, Si; Cheng, Si-Xue; Feng, Jun; Zhang, Xian-Zheng
Abstract : An innovative pre-targeting system based on artificial "biotinylated transferrin-avidin–biotinylated peptide" interaction was established, which was achievable for the tumor cell fluorescence imaging and thereafter targeting therapy from biotinylated pro-apoptotic peptide nano-vesicles. Abstract : A programmed pre-targeting system for tumor cell imaging and targeting therapy was established based on the "biotin–avidin" interaction. In this programmed functional system, transferrin-biotin can be actively captured by tumor cells with the overexpression of transferrin receptors, thus achieving the pre-targeting modality. Depending upon avidin–biotin recognition, the attachment of multivalent FITC–avidin to biotinylated tumor cells not only offered the rapid fluorescence labelling, but also endowed the pre-targeted cells with targeting sites for the specifically designed biotinylated peptide nano-drug. Owing to the successful pre-targeting, tumorous HepG2 and HeLa cells were effectively distinguished from the normal 3T3 cells via fluorescence imaging. In addition, the self-assembled peptide nano-drug resulted in enhanced cell apoptosis in the observed HepG2 cells. The tumor cell specific pre-targeting strategy is applicable for a variety of different imaging and therapeutic agents for tumor treatments.